Moving the Mountain: Beyond ground Zero to a New vision of Islam in America By Imam Feisal Abdul Rauf (New York: Free Press, 2012. 240 pages.) (American Journal of Islam and Society, 2014)
Few are as qualified as Imam Feisal Abdul Rauf to articulate a vision forAmerican Muslims. He has been involved with several major institutionbuildingprojects to address the concerns of American Muslims; his wife,Daisy Khan, has also participated in some of these projects. Since 1983, hehas served as imam of New York City’s al-Farah Mosque and thus is ratherfamiliar with the achievements, struggles, and diversity of the American-Muslim experience. His involvement with one of this community’s mostformative post-9/11 undertakings, the Cordoba House Project (also knownas Park 51 and the Ground Zero Mosque), attracted national and internationalattention.Several other American Muslims have written about the community. Forexample, James Yee’s For God and Country (2005), Sumbul Ali-Karamali’sThe Muslims Next Door (2008), and Asma Nomani’s Standing Alone in Mecca(2006) have experienced modest mainstream success. Mucahit Bilici’s FindingMecca in America (2012) is a notable, although a more academic, work.Imam Rauf’s book belongs to the first genre. Aimed at a general audience, itprovides a good understanding of such issues as jihad and gender relations inIslam, the Shari‘ah, and American-Muslim identity formation.Book Reviews 127The author’s key idea is that American Muslims are on their way to creatinga unique identity, one that is true to the spirit of Islam and also fits intoAmerican cultural norms. If fully realized, this identity would have threemajor potential benefits: making the United States more tolerant and just,healing the wounds between it and the broader Muslim world, and inspiringMuslims everywhere to reclaim Islam from the extremists. According toRauf, this identity can only be fully realized if Muslims have a good understandingof Islam, uphold American laws, and engage in the country’s ongoingmulti-faith projects ...